Implikasi Etika Solidaritas Knud Ejler Løgstrup terhadap Korban Virus Covid-19 di Indonesia - Sobon, Kosmas; Ehaq, Timoteus Ata Leu (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2021)
The purpose of this article is to understand and analyze critically and sharply about the solidarity’s ethics of Knud Ejler Løgstrup and its implications for the victims of covid-19 in Indonesia. The research method is library research using the hermeneutic method. The results of research showed Løgstrup's thought of solidarity became the basis for solidarity on victims of desease covid-19, solidarity on victims of covid-19 was not just a feeling, it was not normative, always asymmetrical, a moral phenomenon and the hallmark of love.